La correcta clasificación de las personas privadas de libertad en función al perfil criminológico y el manejo de los Centros de Privación de Libertad. - Ocampo Arana, Jonathan Alexander (2023)
The present investigation is titled "The correct classification of persons deprived of Liberty Based on the criminological profile and the Management of Prisons" The present study has been conducted because multiple shortcomings have been evidenced, which crosses the Ecuadorian prison system. Reason for which the purpose of this investigation is to describe if the implementation of the criminological profile in the classification of persons deprived of liberty helps to better manage the centers of deprivation of freedom and the proper rehabilitation of those deprived of liberty. Because of that, the present investigation has three units for the treatment of the theoretical framework: the first, centers of deprivation of liberty, where essential aspects of the types of centers of deprivation of liberty are dealt with, as well as the tools used. And the situation of the Ecuadorian prison system, the second, referring to aspects of the criminological profile as well as its classifications and sub-classifications; and, finally, the third, on rehabilitating persons deprived of their liberty. In this regard, a bibliographic, non-experimental-descriptive research design has been used through inductive, descriptive, and analytical research methods with a hybrid approach; Regarding the research design, this is part of a bibliographical investigation, not experimental-descriptive. In addition to this, it has been possible to collect information thanks to the research instruments that allowed me to develop conclusions and recommendations according to the investigated problem.